The Prominent Role of Hematopoietic Peptidyl Arginine Deiminase 4 in Arthritis: Collagen‐ and Granulocyte Colony‐Stimulating Factor–Induced Arthritis Model in C57BL/6 Mice. Issue 7 (7th June 2022) - Fukui, Shoichi; Gutch, Sarah; Fukui, Saeko; Cherpokova, Deya; Aymonnier, Karen; Sheehy, Casey E.; Chu, Long; Wagner, Denisa D.
Abstract : Objective: Genome‐wide association studies have connected PADI4, encoding peptidylarginine deiminase 4 (PAD4), with rheumatoid arthritis (RA). PAD4 promotes neutrophil extracellular trap (NET) formation. This study was undertaken to investigate the origin of PAD4 and the importance of NET formation in a C57BL/6 mouse model of arthritis. Methods: To permit the effective use of C57BL/6 mice in the collagen‐induced arthritis (CIA) model, we introduced the administration of granulocyte colony‐stimulating factor (G‐CSF) for 4 consecutive days in conjunction with the booster immunization on day 21. Mice with global Padi4 deficiency ( Padi4 −/− ) and mice with hematopoietic lineage–specific Padi4 deficiency ( Padi4 Vav1Cre/+ ) were evaluated in the model. Results: G‐CSF significantly increased the incidence and severity of CIA. G‐CSF–treated mice showed elevated citrullinated histone H3 (Cit‐H3) levels in plasma, while vehicle‐treated mice did not. Immunofluorescence microscopy revealed deposition of Cit‐H3 in synovial tissue in G‐CSF–treated mice. Padi4 −/− mice developed less severe arthritis and had lower levels of serum interleukin‐6 and plasma Cit‐H3, lower levels of Cit‐H4 in synovial tissue, and less bone erosion on micro–computed tomography than Padi4 +/+ mice in the G‐CSF–modified CIA model. Similarly, Padi4 Vav1Cre/+ mice developed less severe arthritis, compared with Padi4 fl/fl mice, and presented the same phenotype as Padi4 −/− mice. Conclusion: We succeeded in developing an arthritis model suitable for use in C57BL/6 mice that is fully compliant with high animal welfare standards. We observed a >90% incidence of arthritis in male mice and detectable NET markers. This model, with some features consistent with human RA, demonstrates that hematopoietic PAD4 is an important contributor to arthritis development and may prove useful in future RA research.